Projections of nucleus accumbens adenosine A2A receptor neurons in the mouse brain and their implications in mediating sleep-wake regulation - Zhang, Jianping; Xu, Qi; Yuan, Xiangshan; Chérasse, Yoan; Schiffmann, Serge N.; De Kerchove D'ExaErde, Alban; Qu, Weimin; Urade, Yoshihiro; Lazarus, Michael; Huang, Zhili; Li, Ruixi (Frontiers in Neuroanatomy, 2013)
Adenosine A2A receptors (A2ARs) in the nucleus accumbens (Acb) have been demonstrated to play an important role in the arousal effect of adenosine receptor antagonist caffeine, and may be involved in physiological sleep. To better understand the functions of these receptors in sleep, projections of A2AR neurons were mapped utilizing adeno-associated virus (AAV) encoding humanized Renilla green fluorescent protein (hrGFP) as a tracer for long axonal pathways. The Cre-dependent AAV was injected into the core (AcbC) and shell (AcbSh) of the Acb in A2AR-Cre mice. Immunohistochemistry was then used to visualize hrGFP, highlighting the perikarya of the A2AR neurons in the injection sites, and their axons in projection regions. The data revealed that A2AR neurons exhibit medium-sized and either round or elliptic perikarya with their processes within the Acb. Moreover, the projections from the Acb distributed to nuclei in the forebrain, diencephalon, and brainstem. In the forebrain, A2AR neurons from all Acb sub-regions jointly projected to the ventral pallidum, the nucleus of the diagonal band, and the substantia innominata. Heavy projections from the AcbC and the ventral AcbSh, and weaker projections from the medial AcbSh, were observed in the lateral hypothalamus and lateral preoptic area. In the brainstem, the Acb projections were found in the ventral tegmental area, while AcbC and ventral AcbSh also projected to the median raphe nucleus, the dorsal raphe nucleus, and the ventrolateral periaqueductal gray. The results supply a solid base for understanding the roles of the A2AR and A2AR neurons in the Acb, especially in the regulation of sleep.